An Epigenetic Signature is Associated with Serum 25‐Hydroxyvitamin D in Colorectal Cancer Tumors. Issue 18 (3rd August 2021) - Boughanem, Hatim; Izquierdo, Andrea G.; Hernández‐Alonso, Pablo; Arranz‐Salas, Isabel; Casanueva, Felipe F.; Tinahones, Francisco J.; Crujeiras, Ana B.; Macias‐Gonzalez, Manuel
Abstract : Introduction: Vitamin D has been widely associated with colorectal cancer (CRC) through different insights. This study aims to explore the association between serum 25‐hydroxyvitamin D (25(OH)D) and the global DNA methylation in tumor from CRC patients. Methods and Results: A genome‐wide DNA methylation analysis is conducted in 20 CRC patients under categorical (10 patients have 25(OH)D <30 ng mL −1 ; 10 patients with 25(OH)D ≥30 ng mL −1 ) and continuous models of 25(OH)D. A total of 95 differentially methylated CpGs (DMCpGs) are detected under the categorical model (false discovery rate (FDR) < 0.05), while 16 DMCpGs are found under the continuous model. Regional analysis showed eight vitamin D‐associated differentially methylated regions (DMR). Between them, a DMR is the most significant at cAMP‐Dependent Protein Kinase Inhibitor Alpha ( PKIA ) locus. Furthermore, seven genes, including PKIA gene, have more or equal than two significant DMCpGs. The protein networking analysis found pathways implicated in cell adhesion and extracellular matrix, as well as signaling transduction. Conclusions: This study identifies novel epigenetic loci associated with serum 25(OH)D status. Interestingly, also, a positive association between vitamin D and DNA methylation in the CRC context is found, suggesting a role in CRC. Further studies are warranted to clarify and replicate these results. Abstract : Low serum 25‐hydroxyvitamin D (25(OH)D is associated with decrease global DNA methylation in the colorectal cancer context. This approach provides gene candidates that are associated with 25(OH)D, to consider as epigenetic mark.